The CRC Press terrorism reader - Maras, Marie-Helen, 1979- (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2014)
'From CRC Press's unrivaled pool of author experts comes the ultimate reader on terrorism. This book covers real-world threats and solutions for how to counter, prepare for, mitigate, manage, and respond to terror threats and acts. It looks at a number of global groups, paying particular attention to domestic attacks. Special emphasis is placed on tactics of both terrorists and counter-terrorists. It covers policy issues, critical infrastrucrue protection, terrorism funding, target selection, and other essential topics. Also discussed are weapons of mass destruction, intelligence/antiterrorism efforts, and terrorism crisis management and responder issues.'--
'Introduction From the best and brightest of CRC Press' unrivaled pool of author experts comes the ultimate reader on terrorism. This volume serves as a perfect complement to any course in Homeland Security, Terrorism, or Criminal Justice curricula because it provides not only a history and background of terrorism, but also covers: important policy issues; critical infrastructure protection as it relates to terrorism; terrorism funding; global and domestic groups; transnational terrorist activities, surveillance, planning, and tactic and target selection; weapons of mass destruction; intelligence; antiterrorism efforts; terrorism crisis management and responder issues; regional security issues; and current trends in terrorism and counterterrorism. Unlike other books on the market that cover only theory or history, this volumes considers the essentials of terrorism as well as real-world threats and solutions as to how to counter, prepare for, mitigate, manage and respond to terrorist threats and acts. As such, it is far more practical than the average survey book -- this is practitioner knowledge from the field straight into the reader's hands. The primary goal of this book is to give readers an understanding of what terrorism is, the terrorist threat, ways to prevent, mitigate, and deter attacks, and best practices with which to respond to and mitigate the impact of disasters. To accomplish this, it introduces readers to: the various definitions of terrorism; key terrorist global and domestic terrorist organizations and discuss the varying motivations behind these groups;'--
Includes bibliographical references and index.
Keywords: Terrorism; Terrorism -- Prevention